PENENTUAN KEPUTUSAN MULTI KRITERIA DENGAN HIMPUNAN SAMAR - Samsuryadi - (Jurnal Sistem Informasi, 2009)
Decision support systems to solve multi-criteria problems can use fuzzy set approach. Fuzzy set operations used in this article are the average operating vague (arithmetic mean) and slices of vague, like a fuzzy standard, Einstein product and algebraic product. The results showed that the ability to explain the criteria of incision surgery better than the arithmetic mean operation. Â  Keywords: rerata aritmetika, standard fuzzy, Einstein product, algebraic product.